1937
DOI: 10.1002/hlca.193702001201
|View full text |Cite
|
Sign up to set email alerts
|

Sur la production de l'ozone par l'électrolyse. Electrolyse à basse température

Abstract: Me t h y l g l u c o s i d d e r S t r o p h a n t h o t r i o se . Dasselbe ents teh t bei der Met hanolyse von Hep taee tyl-k-s trophant hosid (siehe 4. Abschnitt). Es krystallisiert aus Alkohol-Ather in iiusserst feinen quadratischen Blattchen, die sich, von der Seite gesehen, wie Nadeln aneinander schachteln. Das Methylglucosid ist spielend loslich in Wasser, loslich in Alkoholen und unloslich in Chloroform, Ather, Petrolather, Benzol, Essig-ester. PehZing'sche Losung wird vom Methylglucosid nicht reduzier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

1941
1941
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…It was realised very early in the research on electrochemical ozone generation that low temperatures favoured higher ozone current efficiencies at Pt and Pt-based electrodes (Briner, 1937;Briner and Yalda, 1942;Lash et al, 1951;Seader and Tobias, 1952), an observation later confirmed using other anode materials; e.g. PbO 2 (Amadelli et al, 2000;Da Silva et al, 2001;Foller and Tobias, 1982) and carbon (Foller and Kelsall, 1993).…”
Section: The Effect Of Temperature On the Electrochemical Generation ...mentioning
confidence: 88%
See 1 more Smart Citation
“…It was realised very early in the research on electrochemical ozone generation that low temperatures favoured higher ozone current efficiencies at Pt and Pt-based electrodes (Briner, 1937;Briner and Yalda, 1942;Lash et al, 1951;Seader and Tobias, 1952), an observation later confirmed using other anode materials; e.g. PbO 2 (Amadelli et al, 2000;Da Silva et al, 2001;Foller and Tobias, 1982) and carbon (Foller and Kelsall, 1993).…”
Section: The Effect Of Temperature On the Electrochemical Generation ...mentioning
confidence: 88%
“…Briner et al, electrolysed a 5.0 M H 2 SO 4 eutectic solution using a Pt anode, obtaining a maximum current efficiency of 8.5% at -67 C (Briner, 1937). Putnam et al, obtained a maximum current efficiency of 19.4% by electrolysing a 30% HClO 4 solution at -50 C using a Pt anode; however, they found significantly lower efficiencies using H 2 SO 4 at temperatures down to -62 C, in contrast to the results reported by Briner and co-workers .…”
Section: The Effect Of Temperature On the Electrochemical Generation ...mentioning
confidence: 99%
“…The first is probably produced by discharge of water by a similar mechanism to oxygen formation and the formation of ozone by electrolysis of concentrated potassium hydroxide solutions at low temperature (22). The initial increase in overvoltage provides the energy for this reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Ozone can be made by the electrolysis of sulfuric acid or perchloric acid solutions (85,86,100,128,155,361,459,497) in concentrations as high as 58 per cent (361). A practical laboratory ozonator of this type has been described (85,86).…”
Section: Utilization Of Ozonationmentioning
confidence: 99%